2023
DOI: 10.1007/s12035-023-03445-1
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol

Abstract: The mechanism by which general anesthetic drugs modify the state of consciousness remains unidenti ed. In essence, the Nucleus Accumbens(NAc)may be directly engaged in the principle of general anesthesia. However, it is uncertain whether NAc GABAergic neurons play a role in the propofol-induced general anesthesia effect. MethodsWe used immuno uorescence and Western blotting to access the activities of NAc GABAergic neurons during propofol anesthesia, and then we utilized chemogenetic and optogenetic methods to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Besides, behavioral results showed that after the stimulation, the emergence time was much longer but the induction time did not differ. These findings suggest that the nucleus accumbens GABAergic neurons regulate the progress of induction and emergence ( Yan et al, 2023 ).…”
Section: Basal Forebrainmentioning
confidence: 93%
“…Besides, behavioral results showed that after the stimulation, the emergence time was much longer but the induction time did not differ. These findings suggest that the nucleus accumbens GABAergic neurons regulate the progress of induction and emergence ( Yan et al, 2023 ).…”
Section: Basal Forebrainmentioning
confidence: 93%
“…According to prior experimental studies [ 32 , 33 ], chemogenetic virus was injected into the VGLUT1 mice’s CA1 region 3 weeks before anesthesia/surgery, followed by intramedullary fixation of tibial fractures. Before electrophysiological recording, immunofluorescence and behavioral tests post-anesthesia/surgery, the virus was activated by intraperitoneal injection of pre-configured Clozapine-N-oxide (CNO, Sigma-Aldrich, Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%